A criança como Outro: uma leitura ética da Ludoterapia Centrada na Criança - Brito, Rosa Ângela Cortez de (2012)
The Child-Centered Play Therapy, understood not only in the Axline’s original proposal, but also from the VanFleet, Sywulak and Sniscak’s perspective, has as its premise the notion that the play is a ludic dialogue that promotes the expression of feelings and the expansion of possibilities in the child’s life. The therapy would help the child to identify, recognize and express his/her feelings. The therapist should, therefore, have the skills to enable a safe space for the child’s expression. This ability is understood by Amatuzzi as an ethical previous disponibility. For a philosophical perspective of the ethics of the Child-Centered Play Therapy, it is taken as basis the Lévinas’ ethics of radical alterity, who proposed the responsibility as subjectivity’s structure. The ethical condition would be developed by the openness and availability to the Other, towards the Other’s difference. The non-conceptuable levinasian Other, human being’s antecedent and transcendent, establishes an asymmetric relationship with the Same. From these perspectives, it presents the guiding question of this research: what is the place for the radically Other in Child-Centered Play Therapy? To answer this question, the following general objective was traced: analyze the place reserved to the Other in the Child-Centered Play Therapy. The specific objectives are: inquiry the relation between otherness and subjetivity, based on levinasian ethics, in the Child-Centered Play Therapy; to develop a new reading of Child-Centered Play Therapy, based on radically Other. The chosen methodology was the Gadamer’s philosophical hermeneutics, which proposes the fusion of horizons between the author and the interpreter in order to create a new horizon of comprehension. From the similarities between the Person Centered Therapy and the Ethic of radical alterity, developed by Vieira & Freire and Schmid, it is presented as result that there is a place to the levinasian Other in the Child-Centered Play Therapy, as long as the therapist is openness and disponibility to the trauma that represents the arrival of the child in his/her absolute difference. It is also verified that the child who comes to the attendance, therefore, would be understood as the levinasian Other, whom the therapist is called upon to respond. To enable the therapist openness, he/she (the therapist) should experience permanent processes of inadequacy in the face to face relationship with the child. Grateful for the support of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) in the development of this research.